Interface dominated cooperative nanoprecipitation in interstitial alloys - Hongcai Wang (Nature Portfolio, 2018)
The specifics of nanoscale precipitation in steels remain complex. Here the authors combine high-resolution microscopy and atomistic simulations to identify a cooperative growth mechanism leading to the preferential growth of cementite nanoprecipitates along a specific crystallographic direction.